Large-scale landslide and deep-seated gravitational slope deformation of the Upper Scrivia Valley (Northern Apennine, Italy). Issue 2 (14th March 2016) - Sacchini, Alessandro; Faccini, Francesco; Ferraris, Francesca; Firpo, Marco; Angelini, Serafino
Abstract : The Scrivia river is a right tributary of the Po river, the main Italian water course, which flows eastwards into the Adriatic Sea. The head of the Scrivia valley is located in the Northern Apennines, a very short distance from the Ligurian Sea. Its catchment is characterized by landslide areas greater than both the regional and national average. In this work, the causes of this high landslide density have been investigated and a large-scale map of landslide phenomena is produced. Based on geomorphological constraints, several previously unknown deep-seated gravitational slope deformations (DSGSDs) were also identified. DSGSDs have been distinguished in sackungen and lateral spreads. Their characteristics were analyzed in a geographical information system (GIS) environment and compared with landslide distribution. Field surveys, aerial photo-interpretation and GIS analyses led to the production of a large-scale landslide and DSGSD overview map at 1:35, 000. The massive presence of DSGSDs and their connection to landslide distribution and activity raise important implications for both geological mapping and land planning.